Allylic cross-coupling using aromatic aldehydes as α-alkoxyalkyl anions - Yuasa, Akihiro; Nagao, Kazunori; Ohmiya, Hirohisa (Beilstein Journal of Organic Chemistry, 2020)
The allylic cross-coupling using aromatic aldehydes as α-alkoxyalkyl anions is described. The synergistic palladium/copper-catalyzed reaction of aromatic aldehydes, allylic carbonates, and a silylboronate produces the corresponding homoallylic alcohol derivatives. This process involves the catalytic formation of a nucleophilic α-silyloxybenzylcopper(I) species and the subsequent palladium-catalyzed allylic substitution.
Keywords: aldehyde; copper; copper catalysis; cross-coupling; palladium; synthetic method